Early preterm abdominal pregnancy: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Abdominal pregnancies, a rare form of ectopic pregnancy, pose significant risks to themother and fetus. The severity of complications depends on the gestational age at presentation,abdominal pregnancy location, and attachment to abdominal organs.Case presentation: A 38-year-old, para 3+0 gravida 4 presented with abdominal pain and moderatepallor at 30 weeks gestational age, extrapolated from obstetric ultrasound due to an unknown last normalmenstrual period. She was HIV-positive and on highly active antiretroviral therapy. She had a history oforal contraceptive use before conception. Ultrasound revealed a viable intraabdominal pregnancy at 30weeks with the placenta attached to the mesentery in the right upper quadrant with a nongravid uterus.She was transfused with four units of packed red blood cells before elective laparotomy. Intraoperatively,the gestational sac in the upper quadrants and membranes were ruptured. A live male infant wasdelivered, weighing 990g, Apgar scores of 8 at 1 and 9 at 5. The placenta, which was attached to the leftfallopian tube and the broad ligament was extracted. The infant was admitted to the newborn unitbecause of prematurity. The postoperative period was uneventful, and the mother and baby were doingwell at the writing of this abstract.Conclusion: Early preterm abdominal pregnancy should be managed by elective laparotomy to optimizeoutcomes for both the mother and fetus. Cases with limited attachment to the viscera tend to havefavorable outcomes. Neonatal outcome primarily depends on gestational age at delivery.